KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI INDONESIA TAHUN 2010-2019 - Maya Arisanti; Nungki Hapsari Suryaningtyas (Balai Penelitian dan Pengembangan Kesehatan Baturaja, 2021)
Dengue Haemorrhagic Fever (DHF) control focuses on preventation efforts with the mosquito nest eradication movement (PSN). The larva free number (ABJ) is an indicator of the success of PSN and early prevention by ensuring a negative house with Aedes sp. This research is descriptive used secondary data on Indonesia’s health profile in 2010-2019. This study describes cases of DHF, incidence rate and larva free rate (ABJ) for 10 years. The results showed that DHF cases in Indonesia from 2010-2019 fluctuating where the higehest cases occurred in 2016 which was 204.171 cases and the lowest occurred in 2018 which was 65.602 cases. The highest incidence of DHF occurred in 2016 which was 78,85 per 100.000 population. Indonesia’s ABJ for 10 years is still below the target <95% in the range 24,1-80,2%. Transmission of DHF still occurs in Indonesia, this can be seen from the still finding cases of DHF every year and indicators of morbidity due to DHF which is still high above 49 per 100.000 population. The low ABJ affects the occurrence of dengue cases in Indonesia.